Blood Pressure Elevation Timing Following Hysterectomy - Kartiwa Hadi Nuryanto; Kanadi Sumapraja; Marcel Elian Suwito; Eka Rusdianto Gunardi; Seno Adjie; Tofan Widya Utami (National Cancer Center - Dharmais Cancer Hospital, 2022)
Background: Hysterectomy is the most common non-obstetric surgery in adult, reproductive-age women. Hysterectomy with or without ovarian conservation is known to increase the risk of cardiovascular disease. However, only a few studies regarding its immediate and short-term effects on hypertension are available. This study aimed to determine changes in blood pressure after a hysterectomy procedure.Methods: This study is a prospective cohort study of patients who underwent a total hysterectomy procedure with or without ovarian conservation at Cipto Mangunkusumo Hospital, Indonesia, from July 2018 to July 2020. Samples were grouped into patients with total hysterectomy only or hysterectomy with ovarian conservation (HT/HTSOU) and bilateral salpingo-oophorectomy hysterectomy (HTSOB). Statistical analysis was done using paired t-test and Wilcoxon test. Results: There were 80 patients included in this study (40 for each group). A significant increase in all blood pressure components occurred at 12 months after the HT/HTSOU and HTSOB procedures (p < 0.05). After six months of the HTSOB procedure, the increase in blood pressure components only occurred in systolic blood pressure and mean arterial pressure (MAP) (p < 0.05).Conclusions: There was a significant increase in all blood pressure components in the HT/HTSOU and HTSOB group at 12 months following hysterectomy while there was a significant increase in systolic blood pressure and MAP in the HTSOB group at 6 months following hysterectomy.